2021
DOI: 10.1007/s10639-021-10768-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of virtual learning environments: A scoping review of literature

Abstract: The purpose of this scoping review is to isolate and investigate the existing data and research that identifies if the synchronous face-to-face visual presence of a teacher in a virtual learning environment (VLE) is a significant factor in a student’s ability to maintain good mental health. While the present research on this explicit interaction among VLE implementation and student mental health is limited, the material suggests a framework for strong utilization of VLEs. Overall, our research has shown that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 50 publications
1
10
0
1
Order By: Relevance
“…This qualitative research reported that female students with children were struggling to manage daily schedules at home and described having time management di culties; some even discussed the lack of support provided by their partners (17). Evidence from literature demonstrated the negative effect of distanced E-learning on students' mental health, revealing that some students experienced feeling helpless, burdened, and suffering from burnout symptoms (17,33,34). Moreover, boredom and lack of motivation were also challenges encountered by participants of this study.…”
Section: Discussionmentioning
confidence: 98%
“…This qualitative research reported that female students with children were struggling to manage daily schedules at home and described having time management di culties; some even discussed the lack of support provided by their partners (17). Evidence from literature demonstrated the negative effect of distanced E-learning on students' mental health, revealing that some students experienced feeling helpless, burdened, and suffering from burnout symptoms (17,33,34). Moreover, boredom and lack of motivation were also challenges encountered by participants of this study.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, as revealed by Abdulwahed and Nagy ( 2009 ), virtual laboratories are not only used as a substitute to real/hands-on laboratory but they can also be used to supplement the hands-on laboratory and provide effective and rapid learning outcomes in the respective science subject. This virtual laboratory provided clear and enjoyable learning environment as commented by teachers, students and different stakeholders reported by different researchers (Ardac & Akaygun, 2004 ; Jeschke et al, 2010 ; Özgür, 2020 ; Caprara & Caprara, 2022 ; Leitão et al, 2022 ). For instance, students who started from virtual laboratory seemed to enjoy in the following stages as they were more aware with all stages than other students.…”
Section: Discussionmentioning
confidence: 91%
“…By means of virtual laboratories, students have the opportunity of repeating any incorrect experiments as well as to deepen the intended experiences. Moreover, the interactive nature of such teaching methods which most of them are multimedia and simulations (Bellou et al, 2018 ) offers a clear and enjoyable learning environment (Ardac & Akaygun, 2004 ; Jeschke et al, 2010 ; Caprara & Caprara, 2022 ; Leitão et al, 2022 ). As a result, virtual laboratories are not only used as a substitute to real laboratory but they can also be used to supplement the hands-on laboratory and provide effective and rapid learning outcomes in the respective STEM subjects or courses (Abdulwahed & Nagy, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Attraction toward E-learning and e-assessments among learners and instructors is enhanced manifold (Khan et al, 2021) because the education and learning industry is shifting rapidly towards technical and virtual methods (Almossa, 2021;Caprara & Caprara, 2022;Dhawan, 2020), in particular, it rose as a most viable solution during Covid 19 Pandemic. Computer programming has emerged as one of the essential skills in this period of digital literacy, as every industry becomes technologically proficient and current progressive inventions are dependent on computer software (Contreras & Siu, 2015), giving rise to the mass enrollment of learners in computer programming courses across the world.…”
Section: Introductionmentioning
confidence: 99%